Streo Image Analysis: A New Approach Using Discrete Orthogonal Moments - Pang, Nyuk Khee @ Angeline Pang (2007)
This thesis provides a detailed description of Tchebichef Moments, and investigates its suitability for streo image analysis. The thesis also reviews conventional methods such as the cooperative streopsis, correlation and window-based matching techniques, and compares the performance with Geometric and Tchebichef Moments.